Acute Lymphoid Leukemia After Anti-TNF-alpha Treatment: A Case Report and Review of the Literature - Füsun GEDİZ ÖZDEMİRKIRAN and Bahriye Kadriye PAYZIN and Eyüp ÇOBAN and Korhan Barış BAYRAM and Betül KÜÇÜKZEYBEK (Archives of Rheumatology, 2015)
The efficacy and safety of anti-tumor necrosis factor-alpha drugs have been shown in active ankylosing spondylitis cases that are resistant to traditional disease-modifying antirheumatic drugs. However, it is well known that these drugs may cause some complications as reactivation of tuberculosis and various hematologic malignancies. In this article, we report a 40-year-old male patient with ankylosing spondylitis who developed Philadelphia chromosome-positive acute lymphoid leukemia after treatment with tumor necrosis factor-alpha inhibitors.